BUSINESS PROCESS ANALYSIS OF STUDENT ACTIVITY FUNDING DISBURSEMENT IN A PRIVATE UNIVERSITY IN INDONESIA - JUNITA, Imelda; KRISTINE, Fanny; ZANIARTI, Sri (Journal of process management and new technologies, 2026)
In addition to formal academic activities in university, student activities play an important role in developing students holistically; consequently, an adequate funding process is needed to ensure the smooth running of these activities. A study conducted at a private university in Indonesia showed that the funding disbursement process often involves multiple phases and actors/units and requires complex procedures. This results in inefficiencies, delays, and a lack of transparency. The goal of this study is to analyze the business process of funding disbursement at a private university in Indonesia and propose improvements to the existing business processes. This study used a qualitative approach in which data collection was conducted through semi-structured interviews with people involved in the process. The data was analyzed by mapping the business process based on Standard Operating Procedures (SOPs) and comparing it with the actual process. The findings of this study disclosed several weaknesses in the existing process, including a lack of digital system utilization, no standard processing time, a time-consuming verification phase, and the persistence of manual processes and documents. Business process improvement is then proposed, including a self-verification mechanism using mandatory checklists in a digital platform by student organizations, system automation, real-time status notification, and standardized processing times. To clarify the roles and responsibilities among stakeholders in the process, the Responsible Assignment Matrix (RACI) was developed. Through this process improvement, efficiency and transparency can be increased while a balance between control and operational effectiveness is still maintained.
Keywords: Business process; funding disbursement; SOP; RACI